INOVASI MODEL PEMBELAJARAN PENDIDIKAN JASMANI UNTUK PENELITIAN TINDAKAN KELAS (PTK) - Farida Mulyaningsih (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
Education is a connector of two sides, one individual side is being growing and on the other hand, social value, intellectual, and moral becoming educator responsibility to push the individual. Individual was grew from the day of born and always grows, this development is causality. But, there is normative component, also because educator claims value, this value is functioning of norm as indicator in identifying what obliged, enabled, and prohibited. So, education is the relation of normative between individuals and value. Education is effort of consciousness and planned to realize situation of teaching and learning process that educative participant actively develops self potency to have the power of religious spiritual, self control, personality, intelligence, glory behavior, and skill required by himself, community, nation, and state. One of our educational problems is the teaching and learning process which still weakly. In teaching and learning process, child is unable to be pushed to develop thinking ability. This reality applies to all subjects, therefore is studied about instructional model especially about innovation of physical education to be continued in Classroom Action Research (CAR). Keywords: Physical Education, Innovation Instructional Model, CAR.